Performance Evaluating of Islamic banks in achieving sustainable development Applied research in the Iraqi Islamic Investment Bank and the Development - Hamdan, Khawla Hussein (International Journal of Psychosocial Rehabilitation, 2020)
The paper , in its theoretical aspect ,aims at introducing the Islamic financing and sustainable development while in its practical one ,evaluates the performance of Iraqi Islamic investment bank in accordance with SD dimensions (social, economic, environmental and institutional ).The paper draws some conclusions most important of which is that the Iraqi bank for investment and development has contributed to the achievement of the economic dimension through the contractual credit to finance projects in sectors of mining and construction, transport and storage ,communication ,water and electricity which was (100%,93%,88% and 49% )respectively out of total Islamic banks contribution .As for its contribution to finance projects in sectors of construction ,transport and storage ,communication and mining was (78%,54% and 30%)respectively out of total bank contribution .The bank has contributed to GDP yet, it has not financed the External world . The contribution of cash credit granted to finance projects was less than that of contractual credit .this in turn affected its contribution to GDP. The bank has followed the (Murabaha), forward sale and bills of lading0 methods. The highest proportion of total cash financing was through (Murabaha) method, although it declined in 2015 as compared with 2013. In the social and environmental dimension, both contractual and cash credit contributed poorly to service projects and was less than that to other sectors. As for the institutional dimension, the bank’s employees joined training courses for the purpose of professional capacity building. The bank has also participated in other banking institutions and bought advanced technology including E-payment and set off systems.